2004
DOI: 10.1111/j.1365-2109.2004.01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary carbohydrate-to-lipid ratios on growth, lipid deposition and metabolic hepatic enzymes in juvenile Senegalese sole (Solea senegalensis, Kaup)

Abstract: A study was undertaken to determine the e¡ect of various dietary carbohydrate-to-lipid ratios on growth performance, whole-body composition and tissue lipid content in Senegalese sole (Solea senegalensis) juveniles. Data on the dietary regulation of key hepatic enzymes of the lipogenic and glycolytic pathways (glucose-6-phosphate dehydrogenase, G6PD; malic enzyme, ME; fatty acid synthetase, FAS; pyruvate kinase, PK and glucokinase, GK) were also generated. Four isonitrogenous (crude protein: 52% dry matter (DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
105
7
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(137 citation statements)
references
References 33 publications
24
105
7
1
Order By: Relevance
“…In the present study, significant differences were found for hepatosomatic index among dietary treatments, but there was no clear association with dietary lipid level since L4 and L20 were similar. Hepatosomatic index values reported are in accordance with those found by Dias et al (4) in Senegalese sole but lower than other flatfish species such as turbot (18) and Atlantic halibut (12,16,24) and other marine teleosts such as European seabass (25) and gilthead seabream (29) .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In the present study, significant differences were found for hepatosomatic index among dietary treatments, but there was no clear association with dietary lipid level since L4 and L20 were similar. Hepatosomatic index values reported are in accordance with those found by Dias et al (4) in Senegalese sole but lower than other flatfish species such as turbot (18) and Atlantic halibut (12,16,24) and other marine teleosts such as European seabass (25) and gilthead seabream (29) .…”
Section: Discussionsupporting
confidence: 90%
“…Overall, liver lipids contribute to 0·1 % of final body weight and 1·7 % of total lipid content. Higher liver lipid contents were reported by Dias et al (4) in this species and in species such as turbot (18) and Atlantic halibut (16) . Moreover, Dias et al (4) observed that elevated levels of dietary lipids in Senegalese sole increased liver lipid content and depressed the lipogenic enzymic activity.…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations